The Influence of Marketing Strategies on Sales Turnover of Bengkulu City's Specialty Food Products - Tiara, Tiara; Bahrin, Bahrin; Duharman, Duharman (CV. Generasi Insan Rafflesia, 2025)
Marketing strategy plays an important role in marketing a product. The problems raised in this study are: (1) what is the marketing strategy carried out by traders of typical Bengkulu city pendap food (2) what is the sales turnover of typical Bengkulu city pendap food (3) is there an influence of marketing strategy on the sales turnover of typical Bengkulu city pendap food. This study aims (1) to determine the marketing strategy carried out by traders of typical Bengkulu city pendap food (2) to determine the sales turnover of typical Bengkulu city pendap food (3) is there an influence of marketing strategy on the sales turnover of typical Bengkulu city pendap food. This study aims (1) to determine the marketing strategy carried out by traders of typical Bengkulu city pendap food (2) to determine the sales turnover of typical Bengkulu city pendap food (3) to determine the influence of marketing strategy on the sales turnover of typical Bengkulu city pendap food This study uses quantitative research with a quantitative approach. The population of this study was 20 Bengkulu city's typical pendap traders. Data collection used observation, questionnaires and documentation. The data analysis technique used simple linear regression. From the results of my research, marketing strategies do not have a significant effect on the sales turnover of Bengkulu City's typical food products, this is in contrast to the research conducted by Chairani Putri (2020), with the research title